Energy-efficient and improved productivity of cellulose nanofibril processing in wet disc mill by regulating the cellulose degree of polymerization - Megashah, Liana Noor; Ariffin, Hidayah; Zakaria, Mohd Rafein; Andou, Yoshito; Hassan, Mohd Ali; Tengku Yasim-Anuar, Tengku Arisyah (Elsevier B.V., 2024)
This research highlights the use of superheated steam (SHS) treatment to improve the productivity and reduce the energy consumption of CNF processing. SHS treatment conducted at 150°C for 1 and 2 h (SHS1 and SHS2) contributed to the reduction in degree of polymerization (DP) of cellulose from oil palm empty fruit bunch. Results exhibited that SHS-treatment reduced the viscosity and number of cycles for CNF processing compared to the untreated cellulose (UT). At the end of wet disc mill processing, CNF-SHS2 viscosity was measured at 60 cP, almost five-fold lesser than that of CNF-UT. The productivity of CNF-SHS2 production improved by almost eight-fold compared to CNF-UT, and the energy consumed to produce CNFSHS2 reduced from 60.5 to 7.4 kWh/kg. All CNF samples produced had an average width of about 10 nm and crystallinity between 54 – 62 %. Our results showed that treatment of cellulose by SHS prior to nanofibrillation contributed to energy efficient nanofibrillation process with improved productivity. The potential energy neutral SHS treatment is demonstrated herein by integrating the energy resource available at the palm oil industry towards sustainable CNF production which would promote the commercial potential of this versatile bio-based material.